Severe haematoma of the vulva and defloration caused by goring - Okur, MI; Yildirim, AM; Köse, R (Elsevier Sci Ireland Ltd, 2005)
Haematoma of the vulva may occur following a trauma due to its highly vascular structure. We present a case of haematoma of the vulva caused by goring by a cow. The hymen and vaginal wall were also lacerated. Evacuation of the haematoma and repair of lacerated tissues were successfully performed. (c) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: haematoma; vulva; goring injury; trauma